Nutritional rehabilitation for children with congenital heart disease with left to right shunt - Nehal El-Koofy; Amira M Mahmoud; Aya M Fattouh (The Turkish Journal of Pediatrics, 2017)
Children with congenital heart disease (CHD) are prone to malnutrition. We aimed to assess the nutritional status of infants with CHD and evaluate the role of nutritional counseling. A cohort study included 50 patients with acyanotic CHD causing increased pulmonary blood flow consecutively enrolled from the cardiology clinic in Cairo University Children Hospital. The patients were subjected to clinical evaluation, nutritional assessment with detailed nutritional history, anthropometric measurements and subjective global assessment (SGA) score and complete blood count, serum albumin and total protein assessment. Degree of failure to thrive (FTT) was assessed and nutritional counselling was offered to those patients; followed up for 3 months then re-evaluated. The mean age was (8.6±4.8 months) with male: female ratio 1:1. The overall prevalence of malnutrition was 62%. Fourteen patients had mild FTT and 17 patients had severe FTT [47.1% with mild heart failure (HF) and 47.1% had moderate or severe HF]. All patients with moderate to severe HF had severe FTT and 80% of those with mild HF had severe FTT. Anemia was present in 96% of the patients. Patients with moderate or severe FTT had more severe degree of HF (p < 0.001), more complications (p < 0.001), more frequent hospital admission (p < 0.001) and less optimum breast feeding (p < 0.001). It was found that 76.5% of those with moderate to severe FTT were formula fed (p 0.002) and significantly lower rate of optimum weaning among (p 0.037). There was significant improvement in the anthropometry, the SGA and degree of FTT, level of albumin with decrease in the percent of anemia among the included patients after nutritional rehabilitation. Malnutrition represents serious problem to children with CHD. Nutritional assessment and proper counseling help to improve the nutritional status of those patients.